Unusual 'green' power generation - Chua, Aloysius Weixin. (2009)
This report describes the process and observations for sourcing conventional or unconventional ‘green’ power solutions for Singapore. The whole process involves three stages which are namely research, implementation and analysis. The final focus is on generating and making use of ‘Green’ power generated from the sun (Solar Energy). The resulting energy obtained from a solar panel which we have set up during this experiment was captured using a voltage logger. It was then analysed and processed using a spreadsheet program in combination with MATLAB. A Neural Network then developed in the final stage of this project to do a prediction of low voltage onset timings for future implementation of a solar powered freezer.